Topics in Catalysis - Somorjai, Gabor A.; Thomas, John M.; Freund, Hans-Joachim.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Topics in Catalysis publishes topical collections in all fields of catalysis which are composed only of invited articles from leading authors. The journal documents today$1 (Bs emerging and critical trends in all branches of catalysis. Each themed issue is organized by renowned Guest Editors in collaboration with the Editors-in-Chief. The topical collections focus on emerging areas in the catalysis field as well as presenting key research from international meetings in this field. The journal publishes twenty issues per year. Proposals for new topics are welcome and should be submitted directly to the Editors-in-Chief.s
Keywords: Physical chemistry; Chemical engineering; Catalysis; Pharmacy; Materials science; Catalysis; Physical Chemistry; Pharmacy; Industrial Chemistry/Chemical Engineering; Characterization and Evaluation of Materials